Inclusive Growth : An Application of the Social Opportunity Function to Selected African Countries - Adedeji, Olumuyiwa (IMF Working Papers; Working Paper, 2013)
The inclusiveness of growth depends on the extent of access to economic and social opportunities. This paper applies the concept of social opportunity function to ascertain the inclusiveness of growth episodes in selected African countries. Premised on the concept of social welfare function, inclusive growth is associated with increased average opportunities available to the population and improvement in their distribution. The paper establishes that the high growth episodes in the last decade in the selected countries came with increased average opportunities in education and health; but distribution of such opportunities varied across countries, depending on the country-specific policies underpining the growth episodes.